Connectedness With Nature and Individual Responses to a Pandemic: An Exploratory Study - Haasova, Simona; Czellar, Sandor; Rahmani, Leïla; Morgan, Natalie (Frontiers in Psychology, 2020)
Most recent epidemics have originated in complex human-nature interactions and yet, our knowledge is very limited regarding the psychological aspects of human-nature relationships that underlie individual human responses in times of pandemic crises. We propose that the concept of connectedness with nature and associated individual difference measures offer a relevant and useful lens to inform us about how humans think, feel and behave in such critical times. Our two-wave study, conducted with 486 US residents at the end of March 2020 (wave 1) and 533 US residents at the beginning of May 2020 (wave 2), focuses on the 2020 coronavirus situation. It maps individual responses to the current pandemic in terms of mental representations, behavioral tendencies and perceived impact, and explores the relationships of these constructs to individual levels of connectedness with nature. As this research employs an exploratory methodology, our results provide an account of potential relationships rather than their validation and thus represent an encouraging steppingstone for research on human behavior in the time of a global pandemic. We identify a series of research propositions and questions for systematic future inquiry.